RELATIONSHIP BETWEEN BILINGUAL INSTRUCTION AND LEARNERS’ PERFORMANCE IN ENGLISH AS SECOND LANGUAGE CONTEXT (Journal of Education and Educational Development, 2020)
The prime purpose of this study was to explore a correlation between bilingual instruction in an ESL class and the class performance of the ESL learners at the secondary level. Quantitative research method was used to evaluate the test performance of 60 ESL learners divided into two groups: One was the controlled group (which was given instructions in L2 only) and the other was the treatment group (which was given instructions in both L1 and L2) in Public School settings. Apart from the students, 15 language teachers’ feedback upon their perceptions of L1 usage in L2 classrooms was taken by using the Likert scale feedback forms. The results confirmed that the instructions given bilingually are directly associated to improved learner outcomes and teachers’ responses for the usage of L1 in classrooms showed a strong positive response.